Optimization of Electroplating Thickness Quality at Hip Joint Implant using the Taguchi Method - Sela Angela Putri; Eko Pujiyanto; Joko Triyono (Jurnal Teknik Industri, 2019)
The hip joint is one of the most often used joints by humans in their activities. The hip joint can be impaired if an accident or an illness such as osteoarthritis-affected. It makes the patients need to get implants to restore their productivity. The implant must be biocompatible, bioactive, and have high strength and resilience to prevent damage. The implants in this study were made from 304 Stainless Steel. One of the stages in making implants is the electroplating process. The electroplating method implemented is hard chrome. Some operating conditions that affect the electroplating process and are used as independent variables are the concentration of chromic acid, electrical voltage, and length of coating time. This study aims to Optimization of Electroplating Thickness Quality at Hip Joint Implant. This study uses the Taguchi method to design the experiment and to obtain the optimum electroplating thickness results. ANOVA is used to obtain the effective prediction of the significance level. Process ANOVA was helped Minitab 16. Based on the ANOVA, it is known that the most significant factor for the electroplating thickness is the concentration of chromic acid, the voltage, and the least influential factor is the electroplating time.